Market, Country and World Effects on Regional Equity Market Integration - Hooy, Chee Wooi; Goh, Kim Leng (UI Scholars Hub, 2010)
This study explores the fundamental driving forces of regional equity market integration in a trading bloc. The determinant factors are categorized into market attribute, economic fundamentals and world information. Our sample consists of 26 equity markets of ive regional trading blocs, namely AFTA, CER, EFTA, EU and NAFTA over the period of January 1999 to August 2005. We measure market integration based on pricing errors as proposed by Korajczyk (1996) and Levine and Zervos (1998). Using panel regressions, our results show that equity integration in these trading blocs is driven internally, where only individual-market volatility and economic fundamentals play a signiicant role in the process. Intra-bloc trade is found to enhance regional equity market integration, supporting the notion that regional convergence extends beyond the trade sector that is promoted in the trade agreements. We also document regime shifting effects during stock market crises, where most of these markets became strongly integrated after a regional crisis, but integration was signiicantly weakened during a crisis that affected the world markets. Also, the level of equity market integration differs across trading blocs, where the blocs with a smaller number of country members are relatively more integrated.